2016
DOI: 10.1115/1.4032245
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Modeling and Spectrum Analysis of Macro–Macro Dual Driven System

Abstract: This paper designs a preload adjustable rotary nut ball screw dual-driven micro feed system, due to the elastic property of the feed system has great influence on its own frequency–response characteristics, which can be identified by analyzing the amplitude relationship between the torque input signal and the acceleration output signal. In order to get the structural dynamic of the dual-driven servomechanism, which is first modeled through lumped mass method, the frequency–response characteristics are calculat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…The foremost characteristic of the dual-driven micro-feed mechanism is its capability to demonstrate a stable velocity under a minimal speed difference, without being influenced by the nonlinear friction. Yu and Feng 22 studied the micro-feed feature of a dual-motor servo system by considering the impact of friction. This study focuses on the low-speed characteristics of the dual-driven ball screw mechanism, and it finds that the speed of the screw demonstrates a noticeable crawling phenomenon when the speed of the screw motor is 1 rad/s under the single-driven condition, according to the repeated simulated system parameters.…”
Section: Simulation and Analysismentioning
confidence: 99%
“…The foremost characteristic of the dual-driven micro-feed mechanism is its capability to demonstrate a stable velocity under a minimal speed difference, without being influenced by the nonlinear friction. Yu and Feng 22 studied the micro-feed feature of a dual-motor servo system by considering the impact of friction. This study focuses on the low-speed characteristics of the dual-driven ball screw mechanism, and it finds that the speed of the screw demonstrates a noticeable crawling phenomenon when the speed of the screw motor is 1 rad/s under the single-driven condition, according to the repeated simulated system parameters.…”
Section: Simulation and Analysismentioning
confidence: 99%
“…For the DDMS based on the hydrostatic screw nut pair, Su proposed a numerical model for the flow boundary for the hydrostatic screw [7], and Liu investigated the boundary slip characteristics within the hydrostatic screw under both DDMS and CFDS driving methods [8]. For the DDMS based on the ball screw nut pair, Yu performed a velocity spectrum analysis [9], Du proposed a full component friction identification model [10], and Wang investigated the effect of torque harmonics on the speed fluctuations of linear feed systems at low speeds; compared with CFDS, DDMS avoids the system resonance caused by torque harmonics at certain speed points [11]. These studies have demonstrated that the DDMS has better low-speed micro-feed performance than the conventional drive feeding system (CDFS).…”
Section: Introductionmentioning
confidence: 99%
“…At present, the main method of research on ball screw feed system control technology is to establish a control model and analyze the system dynamic properties according to the model, and then design a controller to meet the control requirements according to the dynamic properties of the system. At present, the commonly used modeling methods include finite element method [2], lumped mass method [3] and hybrid modeling method [4].…”
Section: Introductionmentioning
confidence: 99%